(untitled) (PerCursos, 2025)
To understand how the Physical-Natural Component (CFN) water has been addressed in Postgraduate work in Geography, a State of Knowledge of theses and dissertations in Geography that address this theme, from 1990 to 2024, was carried out. Among the research parameters, 29 works, 24 dissertations and 5 theses were selected. The Federal University of Goiás stood out as a center of research on Water in Geography. The themes that stood out the most were: “Hydrography”, a theme that covered 45% of the investigations, “Analysis of Physical-Natural Themes” with 27.5% and “Teaching of Water, Environment and Perception” with 27.5%. The role of the School as a center of investigations (95%) and the diversified nature of the approach to water, in the tools, languages and methodologies appropriated by teachers and students, were attested. The predominant methodology was participatory research, which took place through classroom observation, lectures, workshops and workshops. The research demonstrates the interest that students have in their surroundings. The teaching of water in Geography should be based on the everyday perception that students carry with them. Through this, they can confront social and natural phenomena, stimulating the formation of geographic thinking. The research has several constructive points in specific analyses, and it is necessary to evolve the academic dialogue of this knowledge already formed, so that the teaching of Water in Geography can evolve.